Safety and efficacy of endobronchial ultrasound-guided transbronchial biopsy of intrathoracic lymphadenopathy - Yang, Huizhen; Kong, Dechang; Zhang, Xiaoju; Li, Xiangnan; Zhang, Quncheng; Zhou, Ruijie (Frontiers in Medicine, 2025)
IntroductionIn clinical practice, endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) often yields small-volume specimens that may be inadequate for full pathological assessment. To overcome this limitation, EBUS-guided transbronchial cryobiopsy (EBUS-TBCB) and transbronchial forceps biopsy (EBUS-TBFB) have been increasingly adopted. This study systematically evaluates their diagnostic performance and safety in intrathoracic lymph node lesions to inform clinical decision-making.MethodsThis retrospective study included patients who presented to Henan Provincial People’s Hospital between July 2018 and August 2025 with mediastinal or hilar lymph nodes of a short-axis diameter ≥ 1 cm on chest computed tomography (CT) or with abnormally increased metabolic activity of lymph nodes on positron emission tomography (PET)-CT. All patients underwent EBUS-TBNA followed by either EBUS-TBCB or EBUS-TBFB. The study aimed to evaluate the diagnostic performance and safety of the combined use of EBUS-TBNA with EBUS-TBCB or EBUS-TBFB for assessing intrathoracic lymph node lesions.ResultsA total of 211 patients were included in this study, of whom 204 received a definitive diagnosis through EBUS-TBNA combined with EBUS-TBCB or EBUS-TBFB. The sensitivity, specificity, positive predictive value, negative predictive value, and overall diagnostic accuracy in differentiating benign from malignant thoracic lymph node lesions were 96.92% (126/130), 100% (81/81), 100% (126/126), 95.29% (81/85), and 98.10% (207/211), respectively. Further analysis revealed no significant difference in diagnostic yield between the combination of EBUS-TBNA with EBUS-TBCB and that with EBUS-TBFB. However, for pulmonary sarcoidosis, the diagnostic rate of EBUS-TBNA combined with EBUS-TBCB was 96.67% (29/30), higher than that of EBUS-TBNA combined with EBUS-TBFB at 87.50% (14/16). Post-procedural hemoptysis was the most common complication, occurring in 4.74% (10/211) of patients. No severe complications such as major bleeding, mediastinal infection, respiratory distress, or hypoxemia were observed.ConclusionEBUS-TBNA combined with EBUS-TBCB or EBUS-TBFB is a safe, minimally invasive technique that achieves a high diagnostic yield for intrathoracic lymph node lesions. By obtaining sufficient and structurally intact tissue specimens, this approach facilitates molecular pathology testing, supports the diagnosis of benign conditions, and enables accurate pathological classification of malignant diseases.